Tremor reduction by subthalamic nucleus stimulation and medication in advanced Parkinson’s disease - Blahak, Christian; Wöhrle, Johannes C.; Capelle, Hans-Holger; Bäzner, Hansjörg; Grips, Eva; Weigel, Ralf; Hennerici, Michael G.; Krauss, Joachim K. (Journal of neurology, 2007)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) has proved to be effective for tremor in Parkinson’s disease (PD). Most of the recent studies used only clinical data to analyse tremor reduction. The objective of our study was to quantify tremor reduction by STN DBS and antiparkinsonian medication in elderly PD patients using an objective measuring system. Amplitude and frequency of resting tremor and re-emergent resting tremor during postural tasks were analysed using an ultrasound-based measuring system and surface electromyography. In a prospective study design nine patients with advanced PD were examined preoperatively off and on medication, and twice postoperatively during four treatment conditions: off treatment, on STN DBS, on medication, and on STN DBS plus medication. While both STN DBS and medication reduced tremor amplitude, STN DBS alone and the combination of medication and STN DBS were significantly superior to pre- and postoperative medication. STN DBS but not medication increased tremor frequency, and off treatment tremor frequency was significantly reduced postoperatively compared to baseline. These findings demonstrate that STN DBS is highly effective in elderly patients with advanced PD and moderate preoperative tremor reduction by medication. Thus, with regard to the advanced impact on the other parkinsonian symptoms, STN DBS can replace thalamic stimulation in this cohort of patients. Nevertheless, medication was still effective postoperatively and may act synergistically. The significantly superior efficacy of STN DBS on tremor amplitude and its impact on tremor frequency in contrast to medication might be explained by the influence of STN DBS on additional neural circuits independent from dopaminergic neurotransmission.
Gesehen am 05.05.2022